Atypical Reaction Media and Organized Systems for the Synthesis of Low-Substitution Sugar Esters - Koumba Ibinga, Sidrine Kerthy; Fabre, Jean-François; Bikanga, Raphaël; Mouloungui, Zéphirin (Frontiers in Chemistry, 2019)
Sugar esters are nonionic surfactants with amphiphilic properties of interest for the formulation of various products in the fields of detergents, foods, medicines, pharmaceuticals, agriculture and cosmetics. The properties of sugar esters depend on their degree of substitution (we consider degrees of substitution between 1 and 3 here) which guides their use. Sugar esters are biodegradable and non-toxic, and the demand for these compounds is high and continuing to increase. Indeed, interest in these compounds stems from the natural origin of the raw materials, the synthetic processes involved and the performance of the final product. The choice of reaction medium is crucial, to facilitate contact between reactants and prevent hydrolysis of the products. In this review, we provide an overview of the processes and synthesis routes for sugar ester production, ionic liquids and deep eutectic solvent as non-usual media or with organized systems.